PRESIDENTIAL ELECTION DYNAMICS: A LITERATURE REVIEW STUDY ON THE INTERNATIONAL COMPARISON BETWEEN INDONESIA AND OTHER PRESIDENTIAL ELECTION COUNTRIES - Loso Judijanto; Anna Maria Gadi Djou; Rika Nurhayati; Agustinus F. Paskalino Dadi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This literature review delves into the intricate dynamics of presidential elections, focusing on an international comparison between Indonesia and other countries from 2015 to 2020. The study explores historical contexts, democratic trajectories, socio-political landscapes, shifting voter dynamics, and the overarching objectives of presidential elections. Indonesia's unique transition to democracy and its impact on electoral processes are examined, highlighting the interconnectedness between the nation's democratic ideals and the dynamics of presidential elections. Socio-political landscapes emerge as crucial determinants, with regional variations, linguistic differences, and socioeconomic factors influencing voter behavior. Shifting voter dynamics are analyzed, emphasizing the role of economic conditions, educational levels, and regional disparities in shaping voter preferences. Thematic organization guides the exploration of overarching election objectives, encompassing campaign strategies, electoral participation, media influences, and more. A comparative lens is applied to discern commonalities and distinctions, synthesizing existing knowledge and contributing to the global discourse on presidential elections. Supported by a rigorous methodology, including a systematic search strategy and quality assessment, this study draws from diverse sources to ensure a robust foundation for cross-national comparisons. In conclusion, the research provides nuanced insights into the factors influencing presidential elections, contributing to a deeper understanding of the intricate dynamics shaping these pivotal democratic processes globally.